Exploring the relationship between dispositional mindfulness and hoarding behavior: A moderated multi-mediation model - Gong, Yanping; Tan, Yuxuan; Huang, Rong (Frontiers in Psychology, 2022)
Hoarding behavior may not only interfere with hoarders’ daily lives but may also endanger the community. However, few studies have investigated the role of personality characteristics in hoarding behavior. We hypothesized that dispositional mindfulness would be negatively associated with hoarding behavior, and tested mechanisms and gender differences in this association. An online survey was conducted in a sample of 533 Chinese adults (262 women, Mage = 26.82; SD = 6.30). Regression-based analyses showed that mindfulness was associated with less hoarding behavior through higher self-esteem and lower emotion dysregulation. Moreover, gender moderated the mediating effect of emotion dysregulation in the association between mindfulness and hoarding behavior. Specifically, the indirect association was only significant for women. These findings provide a deeper understanding of how, why, and for whom dispositional mindfulness is negatively associated with hoarding behavior, they provide support for self-completion theory and the cognitive-behavioral model of hoarding, and they have heuristic value for future research.